2015
DOI: 10.1186/s13287-015-0034-0
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of efficacy of mesenchymal stem cells on locomotor recovery in animal models of traumatic brain injury

Abstract: IntroductionThe therapeutic potential of mesenchymal stem cells (MSCs) for traumatic brain injury (TBI) is attractive. Conducting systematic review and meta-analyses based on data from animal studies can be used to inform clinical trial design. To conduct a systematic review and meta-analysis to (i) systematically review the literatures describing the effect of MSCs therapy in animal models of TBI, (ii) determine the estimated effect size of functional locomotor recovery after experimental TBI, and (iii) to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 83 publications
4
40
0
Order By: Relevance
“…69 Few reports have demonstrated integration of such cells into host tissues, thus suggesting this cell type to be a poor candidate for cell replacement. [70][71][72][73] A recent study with athymic rat TBI and hNSCs ~38% of the transplanted cells expressed NeuN. 74 The duration of differentiation of hNSCs into NeuN positive cells is consistent with a published report that showed ~6-8 weeks were sufficient to induce transplant derived neurogenesis.…”
supporting
confidence: 72%
“…69 Few reports have demonstrated integration of such cells into host tissues, thus suggesting this cell type to be a poor candidate for cell replacement. [70][71][72][73] A recent study with athymic rat TBI and hNSCs ~38% of the transplanted cells expressed NeuN. 74 The duration of differentiation of hNSCs into NeuN positive cells is consistent with a published report that showed ~6-8 weeks were sufficient to induce transplant derived neurogenesis.…”
supporting
confidence: 72%
“…MSCs alone and MSCs seeded into scaffolds improve functional outcome in animal models of stroke and TBI (Kim et al, 2010; Lu et al, 2007; Mahmood et al, 2004a; Mahmood et al, 2005, 2007; Mahmood et al, 2014a; Mahmood et al, 2014b; Peng et al, 2015; Qu et al, 2011; Qu et al, 2008; Xiong et al, 2009). The mechanisms underlying improvement in MSC-induced functional recovery after TBI are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…There are two other meta-analyses that evaluate progenitor cell treatment for traumatic brain injury. In the analysis by Peng et al (55) only behavioral data were extracted from studies in animals that received only human mesenchymal stromal cells (hMSC), limiting the number of studies that could be included. In the meta-analysis by Chang et al (56) studies were included that examined modified and naïve progenitor cells for the treatment of traumatic brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Peng et al . ran a stratified meta-analysis, and found that the quality score of 5 (possible scores from 0–10) correlated with the largest effect sizes (62). However, neither of these meta-analyses used the same quality metrics.…”
Section: Discussionmentioning
confidence: 99%